Disponibilidade hídrica da microbacia do Igarapé Água Boa de Cima, Município de Boa Vista/RR - Mesquita, Simone Patrícia Santos (2023)
The research analyzed water availability in the Igarapé Água Boa de Cima do Bom Intento microbasin, Roraima, focusing on average reference flows for granting and soil coverage. In terms of methodology, the integrated analysis was developed considering the characterization of the elements of the environmental systems, the analysis of the morphometric characteristics of the watershed, the evaluation of occupation processes and the mapping of vegetation types in the region and around the stream under investigation. . The morphometric analysis revealed that the watershed follows a dendritic drainage pattern, with low branching, a straight water course, an elongated shape, relief with little variation, reduced drainage density, low slope slopes and a lower susceptibility to flooding. As for the predominant uses and occupations, they include small properties for recreational purposes, subsistence agriculture, fish farms, livestock farming and grain cultivation. The water quality of the stream is considered excellent for recreation and suitable for human supply. Furthermore, the research addressed the issue of maximum grantable flows, comparing variable values throughout the year, based on reference flows Q90 and Q95, in contrast to the traditional approach of constant values throughout the year. This analysis considered fluviometric data from the study region, pointing to the need to consider seasonality in water availability in springs. Briefly, this study addressed the assessment of available water in the Igarapé Água Boa de Cima microbasin in a comprehensive manner, considering both aspects related to the average quantities of available water and the interactions between land use and water resources. The results have significant implications for environmental management and sustainability in the region, contributing to informed decisions about water use and awareness of the importance of sustainable practices to preserve water resources for current and future generations. Therefore, the study provided a comprehensive view of the watershed, its physical environment, hydrological characteristics and the importance of considering seasonal variation in water resource management.